Light on the Path and Through the Gates of Gold - Collins, Mabel, 1851-1927 (Salt Lake City, UT : Project Gutenberg, 2005)
"Light on the Path and Through the Gates of Gold" by Mabel Collins is a spiritual treatise written in the late 19th century that aims to guide individuals seeking wisdom and enlightenment through Eastern philosophy. This work explores the spiritual journey, discussing the challenges and sacrifices necessary for true understanding and connection with higher knowledge, often drawing on themes of self-reflection, ambition, and the nature of desire. The opening of the work presents a series of profound aphorisms aimed at disciples who wish to navigate the complexities of spiritual growth. It emphasizes the necessity of overcoming personal desires$1 (Bsuch as ambition, comfort, and the need for recognition$1 (Bbefore one can truly begin to understand and communicate with the "Masters" of knowledge. The author stresses the importance of internal peace, detachment from worldly attachments, and the pursuit of a higher state of consciousness. This initial section serves as a foundation, preparing readers for the more intricate lessons that follow about self-sacrifice and the path toward divine wisdom. (This is an automatically generated summary.)s
Release date is 2005-01-05
Produced by Rose Koven, Juliet Sutherland, Edna Badalian and the Online Distributed Proofreading Team
Keywords: New Thought; Theosophy